A study on diagnostic accuracy of modified triple assessment in palpable breast lumps - K., Radha; M., Uma (International Surgery Journal, 2021)
Background: Breast (mammary gland) is a distinguishing feature of class Mammalia. Patients commonly present, complaining of a lump in the breast, pain, and nipple discharge. Although the most common cause of symptoms is benign breast diseases. But as the life expectancy is increasing incidence of carcinoma breast is also increasing. 1.To assess the individual component diagnostic accuracy of MTT. Methods: This was a cross-sectional study involving 50 female patients with palpable breast lumps attending the Surgical Out-Patient of the Department of General Surgery, Government Royapettah Hospital, Kilpauk medical college, Chennai between June 2020 and May 2021 over 12 months, who underwent clinical breast examination (CBE), ultrasonography (USG), and fine-needle aspiration cytology (FNAC). Results: In the study population, the breast tumor is common on the left side account for about overall 53%age of patients. The bilateral tumors are the least common. Fibroadenoma is the most common benign tumor. In our study also similar results were obtained. The next common benign tumor among the study group is a fibrocystic disease of the breast. Analysis of the above results shows that though FNAC has a sensitivity of 90%, it has a positive predictive value of 100%. The study shows that the combined results of the Modified Triple Test are comparable to the histopathological diagnosis of the biopsy specimen. Conclusions: Our study includes assessment of combined diagnostic accuracy of Modified Triple Test in women of more than 30 years of age with a palpable breast lump.